(3GdeLeY GdeDSS ddeYLe GdeagQSs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bOQ GdBLGd hhSY GdBeGd s
(3LeY ajg CSGei TjhNg eQJHkG Ydi bSejf (B: (3GdChd ajef Med Yfg Yf WQjb GdQhGjI hGdKGfi (B:(3ajef CNP Yfg TjFkG Ydi WQjb GdQhGjIs
(3hgh ef GdfhGOQ fbdkG Yf fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdJGQjNs